COMPARISON OF MINI CHOLECYSTECTOMY VERSUS OPEN CHOLECYSTECTOMY IN PATIENTS WITH CHOLELITHIASIS - Dr. Uzair Karim Qasrani; Muhammad Faizan; Zarnab Siddique; Muhammad Khalid (Journal of University Medical & Dental College, 2020)
ABSTRACT